Comparison of Outcomes of Haploidentical Peripheral Blood Stem Cell Transplantation Supported by Third-Party Cord Blood Versus Human Leukocyte Antigen-Matched Sibling Peripheral Blood Stem Cell Transplantation in Hematologic Malignancy Patients - Cheng, Tingting; Chen, Yan; Liu, Yi; Ma, Xia; Zeng, Cong; Chen, Xu; Wang, Shiyu; Xu, Yajing (Frontiers in Oncology, 2022)
Recent studies have shown that haploidentical hematopoietic stem cell transplantation supported by third-party cord blood (haplo-cord-HSCT) results in rapid hematopoietic recovery, low incidences of graft-versus-host disease (GVHD), and relapse of hematologic malignancies. However, few reports on haploidentical peripheral blood stem cell transplantation supported by third-party cord blood (haplo-cord-PBSCT) have been published. To evaluate the outcomes of patients who underwent haplo-cord-PBSCT or human leukocyte antigen (HLA)-matched sibling donor peripheral blood stem cell transplantation (MSD-PBSCT), we retrospectively reviewed the clinical data of patients with hematologic malignancies who underwent haplo-cord-PBSCT (n = 93) or MSD-PBSCT (n = 72) in our hospital from March 2017 to December 2020. In the haplo-cord-PBSCT and MSD-PBSCT groups, the median time for neutrophil and platelet engraftment was 13 vs. 12 days (p = 0.07) and 16 vs. 13 days (p = 0.06), respectively. The 30-day cumulative incidences of neutrophil engraftment were 100.0% and 98.6% (p = 0.12). The 100-day cumulative incidences of platelet engraftment were 96.8% and 98.6% (p = 0.01). The 100-day cumulative incidences of grade II–IV and grade III–IV acute GVHD were 29.1% vs. 23.6% (p = 0.42) and 9.7% vs. 4.2% (p = 0.18). The cumulative incidences of total and moderate/severe chronic GVHD at 1 year were 26.5% vs. 17.4% and 8.1% vs. 4.5%, respectively, and at 3 years were 34.7% vs. 34.3% (p = 0.60) and 13.6% vs. 10.6% (p = 0.49), respectively. The cumulative incidences of relapse at 1 year were 9.3% and 7.2% and at 3 years were 17.0% and 17.0% (p = 0.98). Non-relapse mortality (NRM) at 1 year was 14.6% and 8.6% and at 3 years was 17.4% and 8.6% (p = 0.13) in two groups. The probabilities of overall survival (OS), disease-free survival (DFS), and GVHD-free/relapse-free survival (GRFS) at 1 year were 81.7% vs. 88.6%, 76.1% vs. 84.2%, and 71.7% vs. 79.7%, respectively, and at 3 years were 78.7% vs. 79.0%, 65.6% vs. 74.4%, and 55.5% vs. 63.6%, respectively, in the corresponding group, p > 0.05. In conclusion, for patients with acute myeloid leukemia/myelodysplastic syndrome (AML/MDS) and acute lymphoid leukemia (ALL), haplo-cord-PBSCT results in similar outcomes compared with MSD-PBSCT, and it may be a valid alternative transplantation method.